2010
DOI: 10.1086/656778
|View full text |Cite
|
Sign up to set email alerts
|

Poor Clinical Outcome for Meningitis Caused byHaemophilus influenzaeSerotype A Strains Containing the IS1016‐bexADeletion

Abstract: Following introduction of Haemophilus influenzae type b (Hib) conjugate vaccines, meningitis caused by serotypes other than Hib has gained importance. We conducted active hospital-based surveillance for meningitis over an 11-year period in Salvador, Brazil. H. influenzae isolates were serotyped and analyzed by PCR, pulsed-field gel electrophoresis and DNA sequencing to identify strains with a specific deletion (IS1016) in the bexA gene (IS1016-bexA). We identified 43 meningitis cases caused by non-type b H. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
0
25
0
1
Order By: Relevance
“…Of the 13 Alaska Native children infected during the 2009–2011 outbreak, 6 (46%) had meningitis, 1 (8%) child died, and 1 child had serious neurologic complications following a stroke the child experienced in the hospital. Although clinical disease associated with Hia was often severe, the Hia isolates from this outbreak in Alaska do not exhibit the IS 1016 -bexA partial deletion, a characteristic classically associated with more severe disease ( 12 , 25 ). …”
Section: Discussionmentioning
confidence: 82%
“…Of the 13 Alaska Native children infected during the 2009–2011 outbreak, 6 (46%) had meningitis, 1 (8%) child died, and 1 child had serious neurologic complications following a stroke the child experienced in the hospital. Although clinical disease associated with Hia was often severe, the Hia isolates from this outbreak in Alaska do not exhibit the IS 1016 -bexA partial deletion, a characteristic classically associated with more severe disease ( 12 , 25 ). …”
Section: Discussionmentioning
confidence: 82%
“…Both cases of Hia meningitis reported in the present study required hospitalization and long-term antibiotic therapy; furthermore, both children cleared the infection with some persistent seizure activity and developmental issues. Lima et al (25) reported poorer outcomes in Hia meningitis caused by strains having the IS1016-bexA partial deletion. Both isolates lacked this deletion and were also negative for β-lactamase and that may explain the success in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates characterized in this study were originally collected as part of three separate studies of meningitis and communityacquired UTI that occurred in Salvador, Brazil (26,27). Due to sample loss, only a subset of the UTI isolates were characterized.…”
Section: Methodsmentioning
confidence: 99%
“…As part of an ongoing study of the etiology of meningitis, limited epidemiologic information is recorded, and bacterial isolates are collected from this reference laboratory and then biobanked at the Gonçalo Moniz Research Center. The methodology and results of this study were previously published (27).…”
Section: Methodsmentioning
confidence: 99%